Building the IOT Software Development Strategy for Vietnam Innovation Value Added Services Co., Ltd. during period 2019 – 2024 = Xây dựng chiến lược phát triển phần mềm IOT cho Công ty TNHH cung cấp giải pháp dịch vụ giá trị gia tăng VIVAS trong giai đoạn 2019 - 2014 - Đào, Minh Ngọc (2020)
Aims of research: The authordecided to study and apply basic theory ofstrategy management to build the IOT software development strategy for VIVASduring period 2019-2024 as well as to propose some solutions. The aims of research are: To study the theoryon strategyand the design of an IOT strategy. To synthesize, analyze and evaluate the current situationof software products andapply the theorytobuild the IOT software development strategy at Vivas. To propose some suggestions and solutions for Vivas' IOT software development strategy